High-order resonance enhancing the mass sensitivity of diamond cantilevers - Wen Zhao; Guo Chen; Keyun Gu; Masaya Toda; Yasuo Koide; Meiyong Liao (APL Materials)
Diamond has been demonstrated as an exceptional semiconductor for microelectromechanical system (MEMS) sensors, offering high sensitivity and reliability due to its ultra-wide bandgap energy, superior mechanical properties, and high thermal conductivity. For MEMS resonator-type sensors that rely on frequency shift detection, such as mass sensors, the overall performance, including the sensitivity, speed, resolution, and noise level, is collectively determined by the stability of the resonance frequency. To improve the sensing performance, geometry optimization and nonlinear operation methods have been used, but these methods lead to increased fabrication complexity or increased energy dissipation. In this work, we propose the utilization of high-order resonance modes to enhance the resonance frequency stability of single-crystal diamond (SCD) MEMS resonators, achieving a significant improvement in mass resolution to as low as 0.15 atto-grams at room temperature. This approach offers a streamlined and competitive strategy for advancing the sensing capabilities of MEMS sensors.